2020
DOI: 10.15741/revbio.07.e671
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Por otro lado, la demanda de dicho cultivo coloca a Estados Unidos como el principal mercado de destino de las exportaciones mexicanas con un 90.1 %, lo cual posiciona a nuestro país como el décimo productor mundial de jitomate con una producción de 3'469,707 t•año-1 (SAGARPA/SIAP, 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…It is important to highlight the presence of Bacillus subtilis in the samples with 2 days and 20 cycles of PCC discharge. This is essential from an agricultural point of view since this bacterium is beneficial for plants and is used as a biological control agent and as a promoter of plant growth [62,63]. Furthermore, it was observed that as the cycles and disinfection times increase, this beneficial microorganism is eliminated for the cultures.…”
Section: Analysis Of the Results Of Disinfected Soilsmentioning
confidence: 99%
“…It is important to highlight the presence of Bacillus subtilis in the samples with 2 days and 20 cycles of PCC discharge. This is essential from an agricultural point of view since this bacterium is beneficial for plants and is used as a biological control agent and as a promoter of plant growth [62,63]. Furthermore, it was observed that as the cycles and disinfection times increase, this beneficial microorganism is eliminated for the cultures.…”
Section: Analysis Of the Results Of Disinfected Soilsmentioning
confidence: 99%